Fully 3D Printed Miniaturized Electrochemical Platform With Plug-and-Play Graphitized Electrodes: Exhaustively Validated for Dopamine Sensing - K S Jaya Lakshmi; Ramya K; Khairunnisa Amreen; Sanket Goel (IEEE Open Journal of Nanotechnology)
Globally, a contemporary trend is towards the realization of sustainable, eco-friendly, miniaturized, and cost-effective sensors. This work focuses on developing a plug-and-play device using inexpensive and biodegradable UV resin fed 3D printing stereolithography (SLA) to produce miniaturized microfluidic platforms for electrochemical sensing. The device consists of three compartments designed to accommodate the 3-electrodes according to the need. SLA 3D printing technique solves these restrictions, making sensors reliable, repeatable, and durable. For electrochemical detection at the point of need or as a lab-on-chip (LoC) platform with minimal sample volume, this work attempts to construct a flexible as well as non-flexible microelectrode setup. The analytical capability of the platform is examined by quantifying nanomolar levels of dopamine in human body fluids. Chronoamperometry and cyclic voltammetry on surface-treated graphene-poly lactic acid (g-PLA) microelectrodes modified with gold nanoparticles are carried out utilizing a handheld potentiostat. The designed device has a linear range of 0.1 to 120 nM with limit of detection and limit of quantification of 0.083 and 0.27 nM, respectively. Various electrode characterizations, including scanning electron microscopy, energy-dispersive X-ray spectroscopy, and electrochemical impedance spectroscopy are carried out. The developed device is finally tested for real-time analysis on human blood and serum samples.